(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
In this paper, we analyse the security of the two e-voting systems. We show that the Estonian e–voting system is practically secure and the SERVE system is not secure. To declare that an e-voting system is secure, it must be as secure as the traditional voting system. The reason is that traditional voting methods are considered to be practically secure and do not allow large-scale misbehaviour. This means that e-voting must be secure against large- scale voting-specific attacks and the security properties of e-voting must be justified.